Using a Game to Improve Phishing Awareness - Patrickson Weanquoi; Jaris Johnson; Jinghua Zhang (Journal of Cybersecurity Education, Research & Practice)
Cybersecurity education has become increasingly critical as we spend more of our everyday lives online. Research shows that college students are mostly unaware of the many online dangers. To teach students about cybersecurity using their preferred medium, gaming, we developed an educational 2D game called “Bird’s Life” that aims to teach college students, as well as general interest individuals, about phishing. Players will come to understand phishing attacks and how to avoid them in real-world scenarios through a fun gaming context. The game can be deployed to multiple platforms such as PC, web, and mobile devices. To measure the effect of this game on learning the concepts of cybersecurity, a pre-test, post-test, and online survey were developed and used in the evaluation process. In Spring 2017, the Windows version of the game was used in two courses in our department (CSC1310 Computer Programming I and CSC3332 Fundamentals of Internet Systems). In Spring 2018, it was used in five sections of one general education course (CSC1306 Computer and Its Use I).